Risk and benefit judgment of excreta as fertilizer in agriculture: An exploratory investigation in Rwanda and Uganda. Issue 3 (2nd April 2016) - Ekane, Nelson; Mertz, C. K.; Slovic, Paul; Kjellén, Marianne; Westlund, Hans
ABSTRACT: This research explores the use of psychometric techniques to improve understanding of psychological mechanisms underlying judgment of excreta as fertilizer in agriculture including other excreta-related activities. Participants consisted of environmental health students, smallholder farmers, and traders in rural and urban Rwanda and Uganda. The finding reveals an inverse relationship between risk and benefit judgments. This relationship holds for the three groups of participants with significant risk and benefit correlations of p < .0001. This finding is consistent with other studies in showing that affect plays a key role in risk perception, judgment, and decision-making. Building on this finding, we conclude that individuals with high risk and low benefit judgment for excreta-related practices would eschew them or emphasize strict standards. Individuals with a high benefit and low risk judgment would engage in excreta management practices regardless of the actual risks involved. This finding is relevant for risk communication and risk management as it indicates that individuals do not rely only on risk management information they receive concerning excreta and related risks but also depend, to an extent, on their feelings about these substances when making judgments and decisions regarding the purpose for using excreta as fertilizer and the level of exposure they can tolerate and manage.